Longitudinal tDCS: Consistency across Working Memory Training Studies - Marian E. Berryhill (AIMS Neuroscience, 2017)
There is great interest in enhancing and maintaining cognitive function. In recent years, advances in noninvasive brain stimulation devices, such as transcranial direct current stimulation (tDCS), have targeted working memory in particular. Despite controversy surrounding outcomes of single-session studies, a growing field of working memory training studies incorporate multiple sessions of tDCS. It is useful to take stock of these findings because there is a diversity of paradigms employed and the outcomes observed between research groups. This will be important in assessing cognitive training programs paired with stimulation techniques and identifying the more useful and less effective approaches. Here, we treat the tDCS+ working memory training field as a case example, but also survey training benefits in other neuromodulatory techniques (e.g., tRNS, tACS). There are challenges associated with the broad parameter space including: individual differences, stimulation intensity, duration, montage, session number, session spacing, training task selection, timing of follow up testing, near and far transfer tasks. In summary, although the field of assisted cognitive training is young, some design choices are more favorable than others. By way of heuristic, the current evidence supports including more training/tDCS sessions (5+), applying anodal tDCS targeting prefrontal regions, including follow up testing on trained and transfer tasks after a period of no contact. What remains unclear, but important for future translational value is continuing work to pinpoint optimal values for the tDCS parameters on a per cognitive task basis. Importantly the emerging literature shows notable consistency in the application of tDCS for WM across various participant populations compared to single session experimental designs.